Perspektif siswa terhadap dunia kerja pada program praktik kerja lapangan di SMKN 1 cempaga hulu - Alamsyah, Fajar; Sholichah, Nikmatus (Universitas Madako Tolitoli, 2025)
The purpose of this study was to determine students' perspectives on the world of work in the fieldwork internship program. The method used was descriptive quantitative. The sample for this study consisted of grade XII students who completed a fieldwork internship, and the data were obtained from questionnaire results. The researcher selected 77 students, namely, 31 from grade XII Agribusiness Plantation Crops, 26 from grade XII Visual Communication Design, and 20 from grade XII Motorcycle Engineering, as the sample. The results of this study indicate that the majority of students responded very positively to various aspects of the program. The average percentage of